Challenges in Minority Langage programming in Canada's Eastern Arctic: The Training of Aboriginal Language Interpretor-Translators - Sammons, Susan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis article explains the reasons which led to the creation of Arctic College and presents its external and internal structure and more specifically, the programmes of interpretation and translation (eligibility, course contents, etc.). It gives an account of the first two years of its functioning.